Chemical composition, antioxidative, antimicrobial and anti-cancer activities of Asteriscus graveolens (Forssk) essential oil - Yousfi, Mohamed; Aouissi, Hadjer; Gourine, Nadhir; Wang, Hong; Chen, Xiaochun; Bombarda, Isabelle; Boudjeniba, Messaoud (Oriental Pharmacy and Experimental Medicine, 2018)
This work is devoted to the study of the chemical composition and the evaluation of the biological activities of essential oils (EOs) extracted from the fowers of Asteriscus graveolens Forssk. plant. The EO sample was obtained by hydrodistillation and the chemical composition analysis was performed using GC and GC/MS. The major chemical components characterizing the EO were cis-chrysanthenyl acetate (44.30%) and cis-8-acetoxychrysanthenyl acetate (33.70%). Antioxidant activity was determined using DPPH and Phosphomolybdenum tests. Although the EO presented a weak scavenging activity (420.16 mg/ mL), it exhibited good reducing power using the Phosphomolybdenum assay (0.28 AAEC/mg). The most important antibacterial activity was noted for Bacillus cereus. The oil revealed a remarkable activity against the nine fungi species tested with percentage inhibition up to 94.12% for Fusarium culmorum (BTCR). More important, this work investigated for the frst time the anticancer efect of this EO on two types of cancer cell lines (human liver carcinoma and Rat pheochromocytoma cell lines). The EO showed a high anticancer activity against both tumor cell lines comparing to the positive control.
Keywords: Asteriscus graveolens Forssk; Essential oil; Chemical composition; Antioxidant activity; Antimicrobial activity; Anticancer activity